1989
DOI: 10.1016/0014-5793(89)80207-8
|View full text |Cite
|
Sign up to set email alerts
|

The domain structure of the inhibitor subunit of human inter‐α‐trypsin inhibitor reflects the exon structure of its gene

Abstract: The gene coding for the inhibitor subunit of the human plasma protein complex inter-u-trypsin inhibitor has been cloned. The exon structure of the gene corresponds with the organization of the protein in two distinct inhibitor domains. The exons coding for the inhibitor domains each comprise the complete information for a typical Kunitz-type proteinase inhibitor structure. In contrast to bovine aprotinin, the mature inhibitor protein contains amino acid residues flanking the inhibitor domains on both sides. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…2). Therefore, we conclude that in mouse, as in human (Kaumeyer et al 1986;Salier et al 1987;Vetr et al 1989;Diarra-Mehrpour et al 1990), a single gene (or identically duplicated genes) and mRNA code for a L chain precursor molecule comprised of Alm and bikunin. Likewise, Alm in rat is encoded by a 1.25 kb mRNA (Kastern et al 1986).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2). Therefore, we conclude that in mouse, as in human (Kaumeyer et al 1986;Salier et al 1987;Vetr et al 1989;Diarra-Mehrpour et al 1990), a single gene (or identically duplicated genes) and mRNA code for a L chain precursor molecule comprised of Alm and bikunin. Likewise, Alm in rat is encoded by a 1.25 kb mRNA (Kastern et al 1986).…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the recent characterization of a family of led-related molecules in plasma suggests that more than one function could pertain to IaI family members (Salier 1990). The complex set of mRNAs and genes that encode the led family has recently been described in human (Bourguignon et al 1985;Kaumeyer et al 1986;Salier et al 1987;Gebhard et al 1988;Vetr et al 1989;Diarra-Mehrpour et al 1989, 1990; the information helped clarify the multipolypeptide chain structure of IaI and related molecules (Bourguignon et al 1983;Jessen et al 1988;Enghild et al 1989). One L chain and three H chains are separately synthesized in the liver by four mRNAs which are designated L, H1, H2 and H3, respectively (Salier et al 1987;Diarra-Mehrpour et al 1989;Enghild et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…All share significant structural similarities. In the gene of human LACI, human a-trypsin inhibitor (Vetr et al, 1989), human amyloid precursor (Ponte et al, 1988;Tanzi et al, 1988), bovine pancreatic basic protease inhibitor (Creighton & Charles, 1987), and bovine spleen inhibitor (Creighton & Charles, 1987), the regions coding for the highly conserved cysteine backbone of the Kunitz-type inhibitor domain are organized in one exon. According to the classification scheme of Patthy (1987), all exons of the LACI gene, as well as the exons coding for the inhibitor subunits of all other cloned Kunitz-typc protease inhibitors, are symmetrical and of class 1-1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the genes of bovine pancreatic and spleen inhibitors have shown that on both boundaries of the domains phase 1 introns are found, 108 and phase 1 in trons demarcate the boundaries of the domains in interα-trypsin inhibitor. 109 The module underwent internal tandem duplications in the case of inter-α-trypsin inhib itor and the lipoprotein-associated coagulation in hibitor. 110 The module is joined to the class 1-1 whey protein module in red sea turtle protease inhibitor.…”
Section: Kunitz-type Protease Inhibitor Modulementioning
confidence: 99%